EgmatQuantExpert wrote:

Solution

To find:• Following the given graph, we need to find out the value of f(f(-1))

Approach and Working: • First we need to find f(-1)

o As per the graph, at x = -1, f = 2

o Therefore, f(-1) = 2

• Now, we can write f(f(-1)) = f(2)

o As per the graph, at x = 2, f = 1

o Therefore, f(f(-1)) = 1

Hence, the correct answer is option D.

Answer: DWhy did we choose "x" first as per graph and not "y" highlighted in yellow. Is it by default to use such step, I mean why we didn't consider y = -1 or to some value?

_________________

"Do not watch clock; Do what it does. KEEP GOING."